Measures Introduced in the Slovak Republic in Response to the Public Health Crisis Caused by the COVID-19 Pandemic - Capíková, Silvia; Burda, Eduard; Nováková, Mária (Medicine, Law & Society, 2021)
The SARS-Cov-2 pandemic outbreak in the Slovak Republic in March 2020 required rapid legal response to protect lives and health of inhabitants and new complex challenges emerged. The objective of this paper is an analysis and critical assessment of measures adopted in the field of health law. As most significant problem fields in Slovakia arose: 1/ Legality and hierarchy of measures limiting everyday life and exercise of citizen rights and freedoms; 2/ the scope, proportionality, extent and duration of measures; 3/ adherence to the measures by the public and law enforcement issues. The pandemic unraveled need to innovate the legal framework of contagious diseases control, for example, constitutional emergency regimen, or powers of the Public Health Authority. Established rule of law framework served to safeguarding against some disproportionate or unwanted effects of anti-pandemic measures, however, future development of more sophisticated legal tools to control the pandemic is needed.